Assessment of Residents' Understanding of Potential Ecosystem Services of Phewa Watershed - Thapa, Shivaraj; Shrestha, Subina; Bhattarai, Suman; Miya, Mahamad Sayab; Gautam, Deepak (Journal of Forest and Natural Resource Management, 2020)
Phewa watershed, the second largest natural lake system in Nepal, is considered vital for the well being and economy at local, provincial and national level. Phewa watershed offers multiple benefits to the downstream dwellers involved in tourism, hotel, boating, fishing, irrigation, hydropower, etc. The constant degradation of watershed has become a serious challenge to sustain the watershed. Payment for Ecosystem Services (PES) can be an effective environmental management tool for sustaining ecological and economic benefits, especially in an urban watershed like Phewa. This study has assessed the opportunities for the potentialityof PES in Phewa watershed. It first identified and ranked the tradable ecosystem services along with service providers and beneficiaries using Likert scale. Then, 137 households were surveyed to evaluate their perceptions of payment for ecosystem services and sustainable management of Phewa Lake. The results identified tourism as the major ecosystem service in the watershed followed by biodiversity and sediment retention to control flooding and erosion. Protected and community forests users groups within the watershed area, landowners, and farmers were identified as upstream users or service providers whereas the business owners like boat agencies, hotels and restaurants, drinking water users, and Nepal electricity authority were identifiedas the service beneficiaries of the identified ecosystem service. The challenges associated with implementing PES scheme were the lack of financial resource, lack of institutional organization and marketing for ecosystem services, population growth, lack of coordination between stakeholders, and lack of public participation. Thus, this study showed that education-based activities should be organized to enhance participation of beneficiaries and upstream dwellers. Also, PES policy mechanism with clear guidelines should be formulated for assuring the participation of the community people forthe implementation of PES.